2017
DOI: 10.1111/pcn.12511
|View full text |Cite
|
Sign up to set email alerts
|

Association of premorbid personality with behavioral and psychological symptoms in dementia with Lewy bodies: Comparison with Alzheimer's disease patients

Abstract: Aim The aim of this study was to elucidate the relation between premorbid personality traits and behavioral and psychological symptoms in dementia (BPSD) in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. Methods Forty‐one DLB patients and 98 AD patients were assessed for BPSD using the Neuropsychiatric Inventory (NPI). Each patient's midlife personality traits were rated by a family member using the NEO Five‐Factor Inventory (NEO‐FFI) questionnaire. Results In multiple regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Behavioral and Psychological Symptom Disease (BPSD) can occur due to dementia progression that consists of biological, psychological, and social disturbances [9]. BPSD can be seen as 1) emotional disorder with negative side, such as anger, hopelessness, depression, and low selfesteem; 2) delusions, commonly with self neglect, suspicions, and misidentification; 3) perception disorder such as visual hallucination; 4) impaired motor function either in a form of retardation, such as slow movement and speech, or hypermotor activity such as more frequent movement; 5) change in circadian rhythm like change in sleep pattern; and 6) eating disorder, such as anorexia and hyperphagia.…”
Section: A Dementiamentioning
confidence: 99%
“…Behavioral and Psychological Symptom Disease (BPSD) can occur due to dementia progression that consists of biological, psychological, and social disturbances [9]. BPSD can be seen as 1) emotional disorder with negative side, such as anger, hopelessness, depression, and low selfesteem; 2) delusions, commonly with self neglect, suspicions, and misidentification; 3) perception disorder such as visual hallucination; 4) impaired motor function either in a form of retardation, such as slow movement and speech, or hypermotor activity such as more frequent movement; 5) change in circadian rhythm like change in sleep pattern; and 6) eating disorder, such as anorexia and hyperphagia.…”
Section: A Dementiamentioning
confidence: 99%
“…13 Personality traits have been associated with various aspects of behavioral symptoms. 14,15 A systematic review of the literature up to 2010 found that of the 5 traits and across a range of BPSD, Neuroticism had the most associations with mood and aggression-related symptoms across the studies reviewed. 16 Specifically, 7 out of 18 studies found a significant association between Neuroticism and these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…AD is characterized by specific clinical symptoms and histopathological features. Clinical symptoms include impaired learning and memory and declines in other cognitive functions . Histopathological features include extracellular amyloid deposits that consist of amyloid beta (Aβ) and neurofibrillary tangles that occur due to intracellular accumulation of the hyperphosphorylated microtubule‐associated protein, tau .…”
mentioning
confidence: 99%
“…Clinical symptoms include impaired learning and memory and declines in other cognitive functions. [2][3][4] Histopathological features include extracellular amyloid deposits that consist of amyloid beta (Aβ) and neurofibrillary tangles that occur due to intracellular accumulation of the hyperphosphorylated microtubule-associated protein, tau. [5][6][7] However, not all of the symptoms and features of AD can be explained by accumulation of Aβ and/or hyperphosphorylated tau.…”
mentioning
confidence: 99%